Adsorption and corrosion inhibition performance of Tunbergia fragrans extract on mild steel in acid medium. (2020) - Muthukumarasamy, Kalaiselvi; Pitchai, Sakunthala; Devarayan, Kesavan; Nallathambi, Lawrence
Abstract: The present study describes the application of Tunbergia fragrans extract for inhibition of mild steel corrosion in hydrochloric acid medium. At first the inhibitor was extracted from the plant using ethanol to obtain the crude extract. This crude extract was added into the pickling solution of hydrochloric acid at different concentrations. Then the mild steel corrosion inhibition efficiency of the inhibitor was determined using weight loss method and electrochemical analysis. The results indicated that the plant extract inhibits the corrosion of the mild steel upto 81% in 1 M HCl. The weight loss data obeyed the Langmuir adsorption isotherm which suggested for predominant physical adsorption. Further, the interaction between the inhibitor and the mild steel surface were observed using scanning electron microscopy coupled with energy dispersive spectrum.